Pengembangan Kemitraan Koperasi, Usaha Mikro Dan Kecil (KUMK) Dengan Usaha Menengah/Besar Untuk Komoditi Unggulan Lokal - Dandan Irawan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2018)
Basically a natural partnership will achieve its goal if mutual requirements, mutual reinforcement, and mutual benefit can be maintained and made a strong fundamental commitment among partners. Nevertheless the development seems very slow. The cause is the presence of specific and different conditions and structure factors compared to other countries. Along with that, we still encounter various forms of gaps, such as inequality among regions, among income groups, between sectors, among economic actors, and so forth. The next problem is that in business entities including cooperatives and micro and small enterprises in running their business activities requires business partnerships with medium and large enterprises in order to improve business performance and business scale. While on the other hand our economic conditions and structures are not yet fully conducive to fostering partnerships based on purely business considerations or competitive market motivations but the business partnership of the foundation is strong enough in our country's constitution. Partnerships will work if partners are equally benefiting. Our concept of partnership is like that, although in the short term, there is a party or a party benefiting more from the other side.